Pemahaman Buruh Wanita dan Ibu Rumah Tangga tentang Program Kesehatan dan Implikasinya terhadap Kebijakan Pendidikan - H.M. Saleh Marzuki (Jurnal Ilmu Pendidikan, 2016)
This descriptive study was designed to compare the knowledge of Indonesian factory workers and house wives on health programs. Data were collected by using interviews in Karangploso, Malang, and were then analyzed statistically by t-test and anova. The results indicated that house wives had better understanding of health programs so far implemented, compared to female factory workers. Among the reasons of this situation were differences in the degrees of expose to communication media and the influences of informal leaders. Housewives seemed to have been able to take more advantage in these matters, than female fatory workers